1985
DOI: 10.1111/j.1365-2044.1985.tb10610.x
|View full text |Cite
|
Sign up to set email alerts
|

Excessive dose requirements of local anaesthetic for epidural analgesia

Abstract: SummaryOn tw'o separate occasions, a 78-year-old obese man suffering ,from congestive cardiac ,failure and peripheral vascular disease, required epidural anaesthesia for surgery to his leg. The dosage requirement on the,first occasion was large and much greater than on the second occasion. Reasons.for the difference in dosage are discussed. We suggest an epidural catheter should be inserted 3 cm into the epidural space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Clinical trials have shown that even if the epidural catheter was left 2-5 cm in the epidural space, this was found to provide satisfactory analgesia. However, one trial has shown that if more than 3 cm of the epidural catheter is left in the epidural space, this increases the risk of transforaminal escape [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical trials have shown that even if the epidural catheter was left 2-5 cm in the epidural space, this was found to provide satisfactory analgesia. However, one trial has shown that if more than 3 cm of the epidural catheter is left in the epidural space, this increases the risk of transforaminal escape [4].…”
Section: Discussionmentioning
confidence: 99%
“…The gold standard for identification of the epidural space is the loss-of-resistance technique [4,5]. At the time of this study, we considered the best method to confirm the catheter position in the epidural space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested to thread in a length of at least 4 cm inside the epidural space to prevent inadequate block that might occur due to the movement of the catheter out of the epidural space during traction applied by fi xation to the skin [8]. Conversely, if a greater length of the catheter is threaded in, there is uncertainty regarding the position of the catheter and the possibility of extrusion of the catheter through the intervertebral foramen [16][17][18]; probably this is the reason why a higher incidence of unsatisfactory analgesia was seen with 8-cm insertion in our study (13.3% in the 8-cm group and 6.7% in the 4-cm group). Radiological evidence reported by Bridenbaugh et al [15] also suggested that only 12% of all epidural catheters directed in a cephalad direction actually threaded to the "hoped for" anatomic levels, while 21% of the catheters had a terminal loop, 48% coiled at the insertion site, and 5% went in a caudal direction or migrated out through an intervertebral foramen.…”
Section: Discussionmentioning
confidence: 98%
“…Histopathologic reactions 7 and blockage of the holes at the catheter tip may lead to decreasing flow rates of the local anesthetic solution, impair distribution of the anesthetic, and thus decrease the analgesic effect. 7,8 Hence, a blockade of 1 or more holes at the catheter tip may increase the perfusion pressure with less anesthetic solution delivered to the epidural space. 7,8 A decrease of the tensile strength may facilitate epidural catheter breakage on withdrawal.…”
mentioning
confidence: 99%